Intermittent Preventive Treatment of Malaria in Pregnancy: Assessment of the Sulfadoxine-Pyrimethamine Three-Dose Policy on Birth Outcomes in Rural Northern Ghana - Francis Anto; Ibrahim Haruna Agongo; Victor Asoala; Elizabeth Awini; Abraham Rexford Oduro (Journal of Tropical Medicine, 2019)
Background. Intermittent preventive treatment of malaria in pregnancy with sulfadoxine-pyrimethamine (IPTp-SP) decreases placental parasitaemia and improves birth outcomes. Currently, WHO recommends three or more doses of SP given during antenatal care (ANC), spaced one month apart after 16 weeks of gestation till delivery. This study determined the level of uptake of SP and its association with birth outcomes in rural northern Ghana. Methods. A survey was carried out at the War Memorial Hospital in Navrongo, Ghana, among mothers who had delivered within ten weeks and were seeking postnatal care. Data on time of first ANC, number of visits, receipt of IPTp-SP, and birth outcomes were extracted from the antenatal records of 254 mothers. Mothers were interviewed on their background characteristics and obstetric history. Chi-square tests and logistic regression were carried out to determine association between antenatal indicators, uptake of IPTp-SP, and birth outcomes using Stata version 13. Results. Uptake of three-five doses of SP was IPT3 =76.4%, IPT4 =37.3%, and IPT5 = 16.0%. Receipt of first dose of SP at 16, 17-24, and 25-36 weeks of gestation was 16.9%, 56.7%, and 26.4%, respectively. Taking the first dose of SP during the second trimester allowed for taking ≥3 doses of SP compared to taking the first dose during the third trimester (χ2 = 60.1, p<0.001). Women who made ≥4 visits were more likely to receive ≥3 doses of SP compared to those who made <4 visits (χ2 = 87.6, p<0.001). Women who received ≥ 3 doses of SP were more likely (OR = 3.3; 95% CI: 1.69-6.33) to give birth at term and also have normal weight babies (OR =4.0; 95% CI: 1.98-8.06). Conclusion. Uptake of three or more doses of SP contributed to improved pregnancy outcomes. Increased efforts towards improving early ANC attendance could increase uptake of SP and improve pregnancy outcomes.